Evaluasi Pola Konsumsi Energi Terbarukan: Berdasarkan Analisis Data Konsumsi Nasional - Revina Putri Damayanti; Dinda Ayu Ningsih; Aulia Hummairoh (Raskha Media Group, 2025)
This study evaluates renewable energy consumption patterns in Indonesia based on national data from 2019 to 2023. The main issue addressed is the low proportion of renewable energy use and its unequal distribution across regions. The objectives are to analyze sectoral and regional trends in renewable energy consumption, identify key influencing factors, and develop a dynamic evaluation model for national energy policy. A mixed-method approach with quantitative emphasis was applied, utilizing data from the Central Statistics Agency (BPS) and the Ministry of Energy and Mineral Resources, supported by spatial analysis using Geographic Information Systems (GIS) and spatial regression to assess regional disparities. Results indicate an average annual increase of 5.2% in renewable energy consumption, contributing 12% to total national energy in 2023. The transportation sector showed the fastest growth (22.5% annually), while the household sector remained dominant in absolute terms. Spatial analysis revealed high inequality (Gini index = 0.62), with Java and Bali accounting for the majority of consumption. Key factors include electricity infrastructure affordability (β = 0.34, p < 0.01) and local policy (β = 0.28, p < 0.05). These findings highlight the need for a holistic policy approach to promote a sustainable energy transition that enhances efficiency and supports socio-economic equity.